Synthesis and characterisation of poly (NIPAN-co-AAc) 10% - Abd Sukor, Siti Rohani (2016)
There are vanous routes for administration of drugs includings topical, transdermal, oral, nasal and parenteral. According to the United State Food and Drug Administration (US FDA), topical route is defined as an administration to a particular site on the outer surface of the body such as skin, eyes or ears (Shah et al., 1992). Topical delivery offers several advantages over parenteral or oral delivery which are systemic load of active pharmaceutical ingredients (API), bypasses first-pass metabolism, improving patient compliance and systemic side effects are reduced (Choi et al., 2012). One of the main objectives of delivering active ingredients via skin route is to achieve an effective concentration at a particular skin layer with insignificant disruption to the skin principle barrier (i.e. stratum corneum, SC). (Alvarez-Roman et al., 2004; Choi et al., 2012; Desai et al., 2013; Guglielmini, 2008; Gupta et al., 2013; Pireddu et al., 2015; Shin et al., 2010). The SC layer is a highly organized hydrophobic structure in the outermost part of the skin which act as a defensive barrier that prevent threats from the external environment such as heat, as well as entrance of exogenous microorganism and chemicals